THE SEQUENTIAL STAR FORMATION IN GLOBULAR CLUSTERS - Ryabova, M. V.; Shchekinov, Yu. A. (Одеські астрономічні публікації, 2008)
The results of [O/Na] abundance modelling in globular clusters NGC 2808 and NGC 6752 are presented. The evolutionary scenario allowing to reproduce characteristic observed features of [O/Na] distribution function has been suggested. Slow winds from massive rotating stars are assumed as a producer of chemical anomalies. It is shown, that the abundance pattern in globular clusters can be explained within a model with a limited mixing of stellar wind and surrounding interstellar gas. This means in other words that the second generation stars are born in a vicinity of individual massive stars of the first generation from the heterogeneously distributed material ejected by these stars.